HLA-DMB correlates with antitumor immunity and an improved prognosis in endometrial carcinoma tumors - Xi, Xiaoyu; Zhang, Xiaona; Tang, Jianxin; Fan, Xiumei; Du, Jiexian (Frontiers in Oncology, 2025)
IntroductionEndometrial Carcinoma (UCEC) is a prevalent malignant tumor within the female reproductive system. HLA-DMB, the beta chain of the non-classical MHC class II protein HLA-DM, has been implicated in the progression of various cancers. However, its role in the development of endometrial carcinoma remains unclear. Therefore, we conducted a preliminary exploration of the prognostic value and potential mechanisms of HLA-DMB in uterine corpus endometrial carcinoma (UCEC).MethodsThe differential expression of HLA-DMB was analyzed in 554 tumor samples and 35 normal samples obtained from the TCGA database. The differential expression of HLA-DMB across various cancers, along with immune infiltration analysis, was conducted using the TIMER2.0 database. Additionally, the expression of HLA-DMB in endometrial carcinoma was examined in the GEPIA2 database, along with its relationship to prognosis. Furthermore, TISIDB was utilized to predict the relationships between HLA-DMB and various immune enhancement factors as well as immunosuppressive factors. Gene Ontology (GO) analysis and Gene Set Enrichment Analysis (GSEA) were employed to explore the signaling pathways associated with HLA-DMB in endometrial cancer. Univariate COX regression analysis was performed to identify prognostic factors for endometrial carcinoma (EC), and a multivariate COX proportional hazards regression model was used to confirm that HLA-DMB can serve as an independent prognostic factor for EC. The protein interaction network of HLA-DMB was constructed using the STRING database, and the chemical drugs related to HLA-DMB were predicted through the CTD database. Finally, the expression of HLA-DMB was validated by qPCR and immunohistochemistry.ResultsThe expression of HLA-DMB at both mRNA and protein levels is significantly higher in UCEC tissues compared to normal tissues. Prognostic analyses indicate that increased expression of HLA-DMB correlates with improved patient prognosis, suggesting its potential as an independent prognostic factor for UCEC. Furthermore, in endometrial cancer, elevated levels of HLA-DMB are associated with higher immune infiltration scores and are closely related to various immune-enhancing factors. Mechanistically, HLA-DMB primarily participates in CD22-mediated regulation of B cell receptors (BCR), leading to BCR antigen activation and the production of second messengers. In our drug analysis, we identified several chemical agents associated with HLA-DMB, including cisplatin, dexamethasone, and ethinylestradiol.DiscussionThis study elucidates the function and underlying mechanisms of HLA-DMB in UCEC, providing a potential biomarker and target for immunotherapy in this disease.